Models of Inter-Organizational Logistics Management in Slovenia - Murtič, Sašo; Lisec, Andrej (Promet - Traffic&Transportation, 2015)
Throughout the history, the transportation of goods and related logistics have played an important role in human development and existence. This pertains to numerous interlinked processes, whose management is often linked to social system, international linkages, development of industry, market and market specifics. In modern times, the management of these processes is increasingly bound to globalization of production and market, moving of production to countries with cheaper labour force, environmental protection. The present Slovenian economy depends to a large extent on economies and corporate relations of the European Union and the world. Such inter-connectedness demands frequent transportation of semi-finished and finished goods. By providing timely delivery of goods, transportation consequently enables inter-organizational linkages and individual production, economic, market and other processes. Organizational and inter-organizational management of transport logistics demands profound understanding of transport flows, freight forwarding expertise and knowledge of transport, tax, environmental and other related regulations. Adequate knowledge and mastering of cultural, linguistic, national and other differences is important as well. The presented analysis and evaluation form the basis of the construction of inter-organizational model of logistics management in Slovenia.